A Study on Plant Selection for Green Building Design - Abd. Wahab, Izudinshah; Ismail, Lokman Hakim (Journal of Science and Technology, 2012)
Previous researches show that incorporating natural elements in design has proven a significant result in balancing building indoor environment. Using plant as part of the design has been widely accepted to contribute good thermal impact as shown in bioclimatic design, green roofing system and living wall elements. As there are so many species of plants for selection, this research was carried out to analyze types of indoor plants that have the potential to contribute thermal comfort to their surrounding. Based on the fact that plant leaves are the part where transpiration and guttation take place, plants are categorized into seven types based on their leaves architecture. They were then tested on their impact on surrounding temperature and humidity. Result shows that Linear, Lanceolate and Oblong shaped leaves categories are good in lowering the relative humidity while the categories that are good in lowering the temperature are Linear, Lanceolate, Cordate and Oblong shaped leaves categories. The study was carried out through series of relative humidity and air temperature monitoring of several room casings that consist with the plants. Both relative humidity and air temperature of the rooms with plants were recorded lower compared with the one without plant. Different categories of plants do give good result in relative humidity and air temperature. Thus, with a good combination of plant installation inside or onto building, it may contribute towards providing a good thermal comfort to the occupants.